Prevalence of Entamoeba histolytica and Giardia lamblia in Children in Kadhmiyah Hospital - Ibrahim, Amjed Qays (The Iraqi Journal of Veterinary Medicine, 2012)
In this study we collect 1520 stool samples during the period from September to December 2010 from children whom their ages between 1 month - 12 years. The results showed that the total infection of Entamoeba histolytica was 9.80% , and Giardia lamblia was 1.77%. And the male ratio that infected with Entamoeba histolytica was 9.83% , while the female ratio was 9.74%; and the male infected with Giardia lamblia was 1.51% , while the female ratio was 2.18%. The result showed that the high average of infection with Entamoeba histolytica and Giardia lamblia in age group from 1 month to 2 years. And there is no significance difference between gender and infectivity rate of Entamoeba histolytica and Giardia lamblia under P≤0.05. Also it showed that there were significant relation between Age group and infectivity rate of Entamoeba histolytica and Giardia lamblia.